Ce0.80Sm0.10Ba0.05Er0.05O2-δ multi-doped ceria electrolyte for intermediate temperature solid oxide fuel cells. Issue 1 (January 2017) - Muhammed Ali, S.A.; Anwar, Mustafa; Abdalla, Abdalla M.; Somalu, Mahendra Rao; Muchtar, Andanastuti
Abstract: Novel multidoped ceria (Ce0.80 Sm0.10 Ba0.05 Er0.05 O2-δ ) electrolyte powders were prepared through solid-state reaction at room temperature. Rare-earth and alkaline-earth elements, which include Er, Sm, and Ba, were used as dopants for CeO2 with a total mole ratio of 0.2. Uniaxial die-pressed powder pellets were densified by air-sintering from 1400 °C to 1600 °C for 6 h. The results of X-ray diffraction indicated a pure cubic fluorite crystal structure with a theoretical density of 7.363 g cm −3 . The relative density and grain size of sintered pellets increased with increasing sintering temperature, which was followed by decreased ionic conductivity. Impedance measurements showed that the highest ionic conductivity was 1.86×10 −2  S cm −1 at 800 °C for the sample sintered at 1500 °C.